2019
DOI: 10.1007/s11141-019-09966-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Diurnal and Seasonal Variations in the Atmospheric Electric Field

Abstract: In order to separate global and local effects of atmospheric electricity, measurements of the fair weather electric field were performed in Nizhny Novgorod in 2013-2018. As a result of processing 139 diurnal records from four observation points spaced 6-8 km apart, diurnal variations in the fair-weather atmospheric electric field for different seasons and weekdays (working days and weekends) were studied. The curve of the local diurnal variation is shown to always have two maxima. The evening maximum of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The annual cycle of emissions with maxima in the winter and minima in the summer affecting the land PG measurements (Adlerman and Williams, 1996;Nicoll et al, 2019;Shatalina et al, 2019) are considerable at Świder, as confirmed in the analysis in Sec. 3 (Figs.…”
Section: σ = 4eµqsupporting
confidence: 64%
“…The annual cycle of emissions with maxima in the winter and minima in the summer affecting the land PG measurements (Adlerman and Williams, 1996;Nicoll et al, 2019;Shatalina et al, 2019) are considerable at Świder, as confirmed in the analysis in Sec. 3 (Figs.…”
Section: σ = 4eµqsupporting
confidence: 64%
“…These values can reach 2 kV/m. In [7] daily and seasonal variations of the value of the vertical component of the atmospheric electric field strength were revealed. In [8,9] a correlation between the electric field strength and air pollution was shown.…”
Section: Introductionmentioning
confidence: 99%